Dental treatment and special needs patients (SNPs): Dentist's point of view in selected cities of Malaysia - Bindal, Priyadarshni; Chai, Wen Lin; Bindal, Umesh; Safi, Sher Zaman; Zainuddin, Zahidah; Lionel, Andreas (2015)
This study was aimed to investigate the perception of dental practitioners in Malaysia regarding the treatment needs and the hitches clinicians face in providing dental care to Special Needs Patients ( SNPs) including the challenges faced by them. Self-administered survey forms were distributed to 150 randomly selected private dentists in Malaysia. The survey consists of 16 questions where 13 were close-ended questions and 3 were open-ended questions. The data were analysed using SPSS software version 12.0. Response rate was 68%. 81.4% of the dentists stated that they are willing to treat SNPS and mostly provide emergency treatment, extractions and restorations to SNPs. 87.2% of the dentists encountered less than 5 SNPs within a period of one month, and only 2% of dentists had seen more than 11 patients. 63.7% of dentists were not aware of the act for persons with disabilities. Dentists identified behavioural management, insufficient skills, lack of training, financial issues, time constraint, physical barriers, inadequate referral facilities, inadequate exposure during undergraduate studies and insufficient financial reimbursement were the main barriers to provide dental care to SNPs. Most of the dentists agreed that no ground floor surgery, steps at clinic entrance, no lift to access 1st floor clinic, and lack of equipment as the physical barriers for SNPs to access their clinic. Our results conclude that the training acquired by dentists in special needs dentistry should be enhanced to provide comprehensive dental care to SNPs.